Precision and systematic errors in global helioseismology mode fitting and inversions: Leveraging some 25 years of nearly uninterrupted observations - Korzennik, Sylvain G. (Frontiers in Astronomy and Space Sciences, 2023)
We have on hand some 25 years of nearly uninterrupted high-quality and high-cadence global helioseismic data. The Global Oscillations Network Group (GONG) project has been producing science quality data since 1995, the Michelson Doppler Imager (MDI) started in 1996, and the Helioseismic and Magnetic Imager (HMI) took over in 2010. Fundamental new constraints have been imposed by helioseismic inferences, yet global helioseismology data processing seems somewhat frozen in time for some of its methodologies. I review and discuss some specific aspects of global helioseismology data analysis, with an emphasis on the issues and challenges presented by mode fitting and inversion techniques. I compare and contrast results derived by different fitting methods, whether using different techniques, different lengths of time series, or different fitting parameters, like leakage matrices or the inclusion or omission of the mode profile asymmetry, leading to our current best handle on the residual systematic errors.